Characterisation of patients with chronic obstructive pulmonary disease initiating single-device inhaled corticosteroids/long-acting β2-agonist dual therapy in a primary care setting in England. Issue 1 (28th September 2022) - Czira, Alexandrosz; Banks, Victoria; Requena, Gema; Wood, Robert; Tritton, Theo; Wild, Rosie; Compton, Chris; Duarte, Maria; Ismaila, Afisi S
Abstract : Introduction: Treatment pathways of patients with chronic obstructive pulmonary disease (COPD) receiving single-device dual therapies in England remain unclear. This study describes the characteristics of patients with COPD before initiating treatment with a single-device inhaled corticosteroid/long-acting β2 -agonist (ICS/LABA) in primary care in England. Methods: This is a retrospective, descriptive study of linked primary and secondary healthcare data (Clinical Practice Research Datalink Aurum, Hospital Episode Statistics). Patients with COPD were indexed on first prescription of fixed-dose, single-device ICS/LABA (June 2015–December 2018). Demographics, clinical characteristics, prescribed treatments, healthcare resource use (HCRU) and direct healthcare costs were assessed over 12 months pre-index. Incident users (indexed on first ever prescription) could be non-triple users (no concomitant long-acting muscarinic antagonist at index); a subset were initial maintenance therapy (IMT) users (no history of pre-index maintenance therapy). Results: Overall, 13 451 incident users (non-triple users: 7448, 55.4%; IMT users: 5162, 38.4%) were indexed on beclomethasone dipropionate/formoterol (6122, 45.5%), budesonide/formoterol (2703, 20.1%) or Other ICS/LABA combinations (4626, 34.4%). Overall, 20.8% of incident users had comorbid asthma and 42.6% had ≥1 moderate-to-severe acute exacerbation of COPD pre-index. Baseline characteristics were similar across indexed therapies. At 3 months pre-index, 45.3% and 35.4% of non-triple and IMT users were receiving maintenance treatment. HCRU and direct healthcare costs were similar across indexed treatments. Prescribing patterns varied regionally. Conclusion: Patient characteristics, prior treatments, prior COPD-related HCRU and direct healthcare costs were similar across single-device ICS/LABAs in primary care in England. A high proportion of patients were not receiving any respiratory medication pre-index, indicating that prescribing in primary care in England is more closely aligned with national guidelines than global treatment strategies. Comorbid asthma may have influenced prescribing decisions. Less than half of users had preindex exacerbations, suggesting that ICS/LABA is not being prescribed principally based on exacerbation history.